THE CONCEPT OF SOCIAL STRATIFICATION AND ITS RELATIONSHIP WITH ISLAMIC EDUCATION - Irmawan, Dayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This article aims to explain the relationship between Islamic education and social stratification in Indonesian society. Social stratification, which is divided into layers based on wealth, occupation, and education, affects individuals' positions in society. Islamic education does not recognize stratification, focusing instead on spiritual values and individual piety. This research method employs a literature review to explore ideas from various sources. The discussion highlights the system and dimensions of social stratification, its forms, and the factors influencing it. The correlation between Islamic education and social stratification indicates that education plays a crucial role in social mobility. The Quran, as the primary source of Islamic education, provides a foundation of values to guide society. In conclusion, education is the key to developing individuals' potential to achieve better positions while maintaining spiritual and moral values in a social context. Islamic education aims to shape morally upright and skilled individuals, promoting awareness of individual and social piety.